Neonatal Leukemoid Reaction Caused by Enterococcus Fecalis Septicemia - L, Yang; ZJ, Liu; LQ, Chen; JL, Hu; N, Zou (Archives of Clinical and Medical Case Reports, 2020)
Background: Leukemoid reaction is not uncommon in neonatal period. It is usualy caused by Down syndrome, antenatal corticosteroids, or perinatal infections. The Enterococcus fecalis is a kind of nosocomial opportunistic pathogen and can cause neonatal septicemia with high mortality. However, neonatal leukemoid reaction induced by Enterococcus fecalis septicemiais is relativity rare. Here, we reported a three-day-old newborn suffered from leukemoid reaction caused by Enterococcus fecalis septicemia. Case Description: A three-day old boy was hospitalized in our NICU of the Second Hospital of Dalian Medical University for jaundice and leukocytosis with comphalitis. Blood routine test displayed leukocytosis with immature cells, bone marrow smear examination showed leukemoid reactions, and the secretion of umbilicus culture showed infection of Enterococcus fecalis. Cefathiamidine was administrated for anti-infection. The baby symptoms eased rapidly, and leukocytosis was return to normal gradually. Conclusion: Enterococcus fecalis can cause neonatal septicemia, which can lead to neonatal leukemoid reaction. Early diagnosis and reasonable antibiotics administration are very important to improve the prognosis of neonatal leukemoid reaction.